Th2-Oriented Immune Serum After SARS-CoV-2 Vaccination Does Not Enhance Infection In Vitro - Luan, Ning; Li, Tao; Wang, Yunfei; Cao, Han; Yin, Xingxiao; Lin, Kangyang; Liu, Cunbao (Frontiers in Immunology, 2022)
The relatively lower protection rate of the alum-adjuvanted inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines reminds us of the antibody-dependent enhancement (ADE) phenomenon observed in preclinical studies during the development of vaccines for Middle East respiratory syndrome coronavirus (MERS-CoV) and severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1). In this study, using the S1 segment of the SARS-CoV-2 spike protein or inactivated whole SARS-CoV-2 virus as an antigen and aluminum as an adjuvant, the risk of ADE of infection with T helper 2 (Th2)-oriented immune serum from mice (N=6) and humans (N=5) was examined in immune cell lines, which show different expression patterns of Fc receptors. Neither the immune serum from alum-adjuvanted S1 subunit vaccines nor inactivated SARS-CoV-2 vaccination enhanced SARS-CoV-2 S pseudotyped virus infection in any of the tested cell lines in vitro. Because both of these Th2-oriented immune sera could block SARS-CoV-2 infection without ADE of infection, we speculate that the lower protection rate of the inactivated SARS-CoV-2 vaccine may be attributed to the lower neutralizing antibody titers induced or the pulmonary eosinophilic immunopathology accompanied by eosinophilic infiltration in the lungs upon virus exposure. Adjustment of the immunization schedule to elevate the neutralizing antibody levels and skew adjuvants toward Th1-oriented responses may be considered to increase the efficacies of both inactivated and spike protein-based subunit SARS-CoV-2 vaccines.